Effects of Substitution of Corn with Ground Brown Rice on Growth Performance, Nutrient Digestibility, and Gut Microbiota of Growing-Finishing Pigs - Sheena Kim (Animals, 2021)
The present study was conducted to evaluate the effects of replacing corn with brown rice on growth performance, nutrient digestibility, carcass characteristics, and gut microbiota of growing and finishing pigs. A total of 100 growing pigs (23.80 ± 2.96 kg BW; 10 weeks of age) were randomly allotted to 4 dietary treatments (5 pigs/pen; 5 replicates/treatment) in a randomized complete block design (block = BW) as follows: corn-soybean meal basal diet (CON) and replacing corn with 50% (GBR50), 75% (GBR75), and 100% (GBR100) of ground brown rice. Each trial phase was for 6 weeks. During the growing period, there were no differences on growth performance and nutrient digestibility among dietary treatments. Similarly, no differences were found on growth performance, nutrient digestibility, and carcass characteristics of pigs during the finishing period among dietary treatments. As a result of the beta diversity analysis, microbial populations were not clustered between CON and GBR100 during the growing phase, but clustered into two distinct groups of CON and GBR100 during the finishing phase. In conclusion, brown rice can be added to the diets of growing-finishing pigs by replacing corn up to 100% without negatively affecting growth performance of the pigs; additionally, this may have an effect on changes in pig intestinal microbiota if continued for a long time.